Effect of UVC radiation on the optical properties of thermally treated CR-39 polymer films: A new approach for the use of CR-39 as an optical dosimeter. (February 2021) - Saad, A.F.; Sedqy, E.M.; Ahmed, R.M.
Abstract: A new approach combining UV and thermal treatments has been studied for improved UV dosimetry of CR-39 polymeric detector films. Prior to thermal annealing, the detector films were exposed to radiation from a UV lamp (250–263 nm) at a distance of 1 cm for different durations of 10, 20, 40, 60, 80, and 100 h. Reversing the sequence, other detector films were first thermally treated in a controlled oven at 160 °C for 1 h and then subjected to UV exposure as above. The qualitative impacts of these treatments have been analyzed by means of ultraviolet/visible (UV/Vis) spectrophotometry in the range 190–450 nm, considering optical properties such as absorbance, band-gap energy, and Urbach energy. As controls, CR-39 detector films subjected only to UV treatment and a pristine film were also examined. The obtained results revealed that the methods combining UV and thermal treatments enhanced the absorptivity for short-wavelength UV radiation, depending on the order of the treatments. The pre-treated films (UV exposure followed by thermal annealing) permitted excellent estimation of UV exposure times, as a proxy of UV dose, over the range 10–100 h. Highlights: F0B7 UVC and thermal treatments combined as a new UV detection approach for CR-39 polymer films. F0B7 The UVC and thermal treatments linearly increase the absorptivity for the UVC compared to the other treatments. F0B7 A great enhancement in the values of carbonaceous cluster M and N and a continuous steadily decrease in the E g d and E g i n d values. F0B7 The absorptivity for the short-wavelength UV radiation does alter with the order of treatments. F0B7 This new approach can potentially enable the estimates of UV dose equivalent.